Management of Water Hyacinth Biomass Along with Industrial Effluents Through Mushroom Culturing and Vermicomposting - Anand, Priyanka (My University, 2010)
Water hyacinth is one of the fast growing notorious aquatic weed. However, the weed can be effectively used in the wastewater treatment and in the control of eutrophication and pollution of water bodies, provided the weed can be properly managed. Management through harvesting removal though highly desirable has not been successful. The removed biomass usually proves a nuisance. High water content, accumulation of pollutants like heavy metals and apparent presence of some irritant compounds, make the harvested biomass not very useful. Use of the harvested biomass for mushroom culturing and vermicomposting of the spent substrate is believed to make the use of water hyacinth for wastewater treatment and for the control of pollution of water bodies both feasible and viable. In the present study, use of water hyacinth biomass as substrate along with industrial effluent as supplements in the mushroom culturing and vermicomposting of water hyacinth along with cow dung have been tried. In addition to it, mushroom culturing has also been studied on wheat straw as substrate without adding any supplements for comparison. Mushroom culturing though successful on wheat straw, was found not successful on water hyacinth biomass. In fact, mycelium growth was found to be much more in water hyacinth bags than on wheat straw. But, pinning and fruiting was not achieved in water hyacinth bags may be due to improper environmental conditions. Vermicomposting was carried out on water hyacinth biomass mixed with cow dung in the ratio of 1:3. Constituents of the water hyacinth biomass (may be heavy metals or certain irritant substances specific to water hyacinth biomass) must not be allowing survival of earthworms especially under the stressed environmental conditions like temperature and humidity. A 50-day study of vermicomposting resulted in the reduction in carbon content, total potassium and increase in calcium. The heavy metal concentration (i.e. Cu,Zn, Ni, Cr, Mg, Pb) is found to be less in vermicomposts than in initial feed mixtures.
MT
Keywords: water hyacinth; vermicomposting; mushroom cultivation